A holistic approach to CAKUT (Congenital Anomalies of the Kidney and Urinary Tract) - Giuseppe Masnata (Hygeia Press di Corridori Marinella, 2016)
The urinary tract malformations, today called CAKUT (Congenital Anomalies of the Kidney and Urinary Tract), include a range of morphological and/or functional abnormalities of the kidney and urinary tract diseases, apart from being the main cause of renal failure in children. The frequency of these birth defects is around 2% of pregnancies and many genetic syndromes may include CAKUT: about 500 of them have been described. The CAKUT concern localized alterations at different levels of the urinary system: hydronephrosis, vesicoureteral reflux, duplex collecting system, megaureter, kidney dysplasia. In the approach to the child with CAKUT it is important to identify a population at risk, distinguishing between CAKUT with and without clinical significance, applying a tailored approach to the individual patient, avoiding unnecessary investigations and treatments.